Polıcy On Prohıbıtıon Of Subsıdızed Fuel Tradıng In North Hulu Sungaı Regency, South Kalımantan Provınce - Jumaidi Jumaidi; Agus Sukristyanto; Achluddin Ibnu Rochim (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study delves into the challenges and opportunities surrounding the implementation of subsidized fuel policies in North Hulu Sungai Regency, with a focus on management and distribution. Utilizing qualitative research methods such as interviews, observations, and document analysis, the study identifies obstacles that impede effective policy implementation across legal, social, economic, and administrative dimensions. These findings underscore the intricacies involved in executing such policies within real-world contexts, emphasizing the necessity for a nuanced understanding of local dynamics and stakeholder perspectives to formulate tailored solutions. Moreover, the study explores potential strategies for surmounting these challenges through the diffusion of innovation model. This model emphasizes key aspects such as relative advantage, compatibility, complexity, trialability, and observability. By integrating this model, the study proposes strategies for bolstering policy effectiveness, including cross-sectoral collaboration, capacity building, and knowledge sharing. Ultimately, this research aims to contribute to the successful implementation of subsidized fuel policies in North Hulu Sungai Regency and beyond, providing valuable insights and practical recommendations informed by the diffusion of innovation perspective